Average field‐aligned current configuration parameterized by solar wind conditions. Issue 2 (15th February 2016) - Carter, J. A.; Milan, S. E.; Coxon, J. C.; Walach, M.‐T.; Anderson, B. J.
Abstract: We present the first large‐scale comparison of the spatial distribution of field‐aligned currents as measured by the Active Magnetosphere and Planetary Electrodynamics Response Experiment, with the location and brightness of the average auroral oval, determined from the Imager for Magnetopause‐to‐Aurora Global Exploration far ultraviolet instrument. These distributions are compared under the same interplanetary magnetic field magnitude and clock angle conditions. The field‐aligned currents and auroral oval drop to lower latitudes, as the interplanetary magnetic field becomes both increasingly stronger in magnitude and increasingly southward. We find that the region 2 currents are more closely aligned with the distribution of auroral UV emission, whether that be in the discrete auroral zone about dusk or in the postmidnight diffuse aurora sector. The lack of coincidence between the region 1 field‐aligned currents with the auroral oval in the dusk sector is contrary to expectation. Key Points: FACs and the auroral oval drop to lower latitudes with increasingly stronger and more southward IMF Region 2 currents are more closely aligned with the auroral UV emissions than region 1 The lack of coincidence between the dusk region 1 currents and the auroral oval is surprising